Business Professionalism When Communicating with Foreign Clients in Indonesia - Wulandari, Tine Agustin; Puwaningwulan, Melly Maulin; Anggaswari, Niluh Ayu (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2025)
This research focusing on how is business professionalism conducted according to the type of business communication, which is verbal (oral or spoken and written) and also nonverbal communication, where the parties involved have different cultural backgrounds, more specifically, between Indonesian employees and foreign clients. Through qualitative descriptive method, research findings showed that the definition of business professionalism has changed and vary significantly across different cultures. Indonesian employees may find it difficult to communicate professionally with foreign clients and the challenge increases when they have to use English as a more universal language instead of Bahasa Indonesia. Indonesian employees are advised to learn and adapt both verbal and nonverbal communication according to the culture of their clients. This research is expected to provide a contribution to create stronger business relationships and more effective communication strategies by understanding the roles and characteristics of their foreign clients in an increasingly cutthroat global marketplace.